AVA na EaD: linguagem total e comunicação - Sousa, Robson de (2023)
AVA na EaD - Total Language and Communication is a reflection on communication in virtual learning environments. Faced with the exponential growth of distance education in the last two decades, as a result of the incorporation of this modality of education by higher education institutions, researching the VLE in EaD is an investigative work to understand how this virtual space is configured as a potential environment for communicative practices or extensive. If the VLE is the interface mediated by the world wide web that presents itself as the locus of meetings in DE, it becomes important to look at how it has been perceived by the students of the HEIs. EaD is a valid education modality governed by specific norms of the Ministry of Education (MEC) and the VLE is the space for meetings of the academic community that connects to the HEI, by offering distance courses. Therefore, the investigation of the VLE allows a better understanding of how these environments, given the diversity of interfaces and technological solutions, can collaborate in the creation of a space that has communication as a central concern for the pedagogical conception of another possible VLE: an environment communication virtual. This concern, which has its genesis in the radical nature of communication, seeks in the theoretical-praxeological production of Paulo Freire and Francisco Gutiérrez Pérez, ways to provide answers and envision possibilities in the face of the current scenario of VLE in DE. These paths gain consistency with the theoretical framework of Freire and Gutiérrez, from the works Extension or Communication? (2013) and Total Language (1978). Thus, AVA na EaD - Total Language and Communication used data from the quantitative research of the INEP census and the qualitative netnographic research from SEMESP, added to the bibliographical and documental research for the accomplishment of this dissertation.